Video Streaming for Creative Writing at International Elementary School - Deni Darmawan; Tatat Hartati; Effy Mulyasari (Journal of Education and Learning (EduLearn), 2013)
This study aims at overcoming difficulty in learning language, both in Indonesian Language and English at international elementary school, especially in creative writing. Creative writing as part of human activity is creativity with language medium as prose (narrative, description), poem (old, new and modern), as well as drama (dialogue, role play, and sosio drama). Specific target to be achieved is the design of Video Streaming for all kinds of creative writing in the language of Indonesian and English. This investigation is a continuation of the previos investigation that has managed to make a video leaning in English for Math and Science as integrated learning to early class at international elementary school. The method used follow the principles of developmental reasearch. The firts stage is script writing video streaming through brainstorming with teachers, lecturers, teams of investigators Indonesia (UPI) and Malaysia (USM). The second stage manuscript, making finalization Video Streaming, make the Web, media experts and creative writing material team investigators. The third stage, testing the Video Streaming, Web and dissemination of results into all the international elementary school in Indonesia and Malaysia.